One country, multiple country-related effects: An international comparative analysis among emerging countries on Italian fashion products. Issue 2 (3rd April 2017) - Pucci, Tommaso; Casprini, Elena; Guercini, Simone; Zanni, Lorenzo
Abstract: The purpose of this paper is to understand whether the impact of country image and product-specific country-of-origin over the willingness to pay premium prices is different among consumers from different emerging countries. After a review of the literature shedding light on the heterogeneity of country-related cues, the paper provides first empirical evidence of a cross-national analysis based on data gathered from 2364 consumers belonging to 4 emerging countries (China, India, Thailand and Brazil) and the domestic country (Italy). The data-set was used to verify whether country image (i.e. the image consumers have of Italy as a country) and product-specific country-of-origin image (i.e. the image consumers have of "Made in Italy" fashion products) impact in a different way on the willingness to pay premium prices for Italian fashion products. Results show that country image and product-specific country of origin are country-specific, presenting different roles in the countries considered. Country-related cues in marketing strategies are still an important factor affecting consumer behaviour, especially for certain products. This paper sheds light on how country-related effects for fashion products differ across countries, with implications for both practitioners and researchers.